DEVELOPMENT OF THE PENTAHELIX TO HEXAHELIX MODEL IN RAJAPOLAH TASIKMALAYA HANDICRAFT SMEs - Depy Muhamad Pauzy; Ristina Siti Sundari; Hary Firmansyah (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2026)
This study aims to develop the pentahelix model into a hexahelix model to strengthen woven handicraft Small and Medium Enterprises (SMEs) in Rajapolah, Tasikmalaya. While the pentahelix model emphasizes collaboration among government, academia, businesses, communities, and media, it has not fully addressed challenges related to financing access, innovation sustainability, and SME performance. Therefore, this study introduces financial institutions as a sixth actor, creating a hexahelix framework that integrates banks, cooperatives, investors, and digital financial platforms. Using NVivo 12 Pro to analyze data from in-depth interviews, the findings reveal that financial institutions have not yet become an effective driver of business expansion. Many entrepreneurs remain reluctant to utilize external financing due to concerns about loan requirements, interest obligations, and installment payments, particularly amid uncertain business conditions. The study concludes that the hexahelix model has the potential to strengthen cross-sector collaboration, support the sustainability of culture-based local economies, and enhance SME performance. However, its effectiveness depends on improving entrepreneurs’ financial literacy and ensuring that financial institutions provide accessible and secure financing schemes that address the concerns of handicraft business owners.